Teaching factory-based video learning to enhance vocational hospitality skills - Endra Gunawan; Urip Sulistiyo; Sofyan; Erisa Kurniati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2026)
The persistent mismatch between school-based instruction and industry-required competencies remains a critical challenge in vocational hospitality education, particularly in integrating cognitive mastery with professional soft skills. Existing studies predominantly emphasize technical skill acquisition, leaving a research gap in the development of integrated multimedia-based Teaching Factory (Tefa) models that simultaneously enhance knowledge and behavioral competencies. This study aims to develop and rigorously evaluate a Tefa-based video learning model to address this gap. Employing a Research and Development (R&D) design based on the Alessi and Trollip model, the study involved vocational students in hospitality programs (Class XI PH1 and PH3). Data were collected using expert validation instruments, student usability questionnaires, soft skills observation sheets, and pretest–posttest assessments. Data analysis combined descriptive statistics, gain score analysis, and effect size estimation to ensure robust evaluation. The findings demonstrate high validity (media: 96.25%; material: 98%) and strong practicality (student response >90%; teacher response: 92.6%). Learning outcomes improved significantly (PH1: 5.55→6.55; PH3: 6.32→8.14), with effect sizes of 0.44 (moderate) and 0.80 (large). Notably, the model also enhanced students’ communication and service-oriented soft skills through behavioral modeling. This study contributes a scalable, industry-aligned instructional model that effectively bridges the theory-practice divide in vocational education.